Impacto do uso de simbiótico na evolução de pacientes com neoplasia de vias aéreas e digestivas superiores submetidos a tratamento cirúrgico - Priscilla Ceci Lages (2016)
This is a double-blind clinical randomized study that included individuals with upper air and digestive tract cancer who underwent surgical treatment. Participants were randomized into a treatment with symbiotic or placebo. The aim was to evaluate if the postoperative treatment with symbiotics would be able to interfere with the postoperative outcome of the participants. Thirty-six patients were included, 18 in the symbiotic group and 18 in the placebo. Patients were evaluated by Subjective Global Assessment, anthropometric measurements, and had blood samples drawn to assess TNF- and intestinal permeability by diamine oxidase. The intervention consisted of symbiotic or placebo administration twice a day, for at least five up to seven days postoperatively. During hospitalization, patients were followed to assess postoperative complications and intestinal function. At beginning, the groups were similar regarding the nutritional status, comorbidities, sex, functional capacity by handgrip strength, anthropometric measurements, as well as T stage, time since cancer diagnosis, location of primary tumor and surgical procedure (p> 0.05). After the beginning of the intervention, the groups were still similar, now concerning the variables: time of hospitalization, antibiotic prophylaxis and therapy and incidence of infectious and non-infectious complications (p> 0.05). There were no differences for TNF- neither for diamine oxidase (p> 0.05). Nevertheless, although not significant, the symbiotic group presented the first stool evacuation earlier, had a higher incidence of diarrhea and softer consistency of stools according to the Bristol Stool Scale (p> 0.05). In conclusion, the symbiotic use was not effective to prevent the development of surgical complications, the modulation of the intestinal function and the inflammatory response, in elective surgical head and neck cancer patients.